PENGEMBANGAN MODUL LATIHAN FORGIVENESS UNTUK SISWA SMA DI KOTA MALANG - Ari Dwi Yudhianto; Nur Hidayah; IM Hambali (Pascasarjana Universitas Negeri Malang, 2016)
This research aims to develop a training modules forgiveness based on the appraisement of experts (reviewers) and high school student's response to the training modules forgiveness that have been developed. This study adapting the model development of Borg and Gall (1983), while the structure of the writing module refers to the guide preparation of module which prepared by the Director General module PMPTK (2008). The results of this study are drafting a training module forgiveness for senior high school students in Malang. Based appraisement materials experts, media specialists, and linguists classified as good, according to school counselors classified very good and yield response of students classified as good. So, that these modules worthy be used in the awarding of guidance services in schools. Penelitian ini bertujuan untuk mengembangkan modul latihan forgiveness  berdasarkan penilaian para ahli (reviewer) dan respon siswa SMA terhadap Modul latihan forgiveness yang telah dikembangkan. Penelitian ini mengadaptasi model pengembangan Borg and gall (1983), sedangkan struktur penulisan modul mengacu pada panduan penyusunan modul yang disusun oleh dirjen PMPTK (2008). Hasil penelitian ini adalah tersusunnya modul latihan forgiveness untuk siswa SMA di Kota Malang yang berdasarkan penilaian ahli materi, ahli media, dan ahli bahasa tergolong baik, menurut konselor sekolah tergolong sangat baik dan hasil respon siswa tergolong baik. sehingga modul ini layak digunakan dalam pemberian layanan bimbingan di sekolah.